DEVELOPMENT OF PICTURE WORD CARD MEDIA USING MODELING THE WAY METHOD IN LEARNING ENGLISH VOCABULLARY TO IMPROVE CLASS 4 LEARNING OUTCOMES - Febriyanty, Yessica; Suratno, Suratno; Widagdo, Arif (University of Kuningan, 2024)
This research aims to develop a picture card product and apply a modeling approach to learning English vocabulary, aimed at improving the academic performance of fourth grade students at SDN Wonosari 01, Semarang City. The utilization of picture cards serves to facilitate teachers in delivering English lessons effectively in a classroom setting. These picture cards are organized based on the ADDIE model, which includes phases such as analysis, design, implementation, and evaluation. The rationale behind this study stems from the substandard academic performance of students in English language schools, which can be attributed to various factors, including the lack of diverse learning resources, ineffective teaching methodologies, and insufficient motivation of students towards learning English. The research methodology adopted for this study is quantitative in nature, using a research and development (R&D) framework. Data collection methods included observations, interviews, and questionnaire surveys. The data analysis process involved conducting the normality test, homogeneity assessment, and n-gain evaluation. After examining the findings, picture cards are considered very useful, categorized as “very valuable” to help the learning process. Picture cards were implemented using the modeling-the-way method to make learning more effective and interactive.